Geometric and electronic properties in a series of phosphorescent heteroleptic Cu(I) complexes: Crystallographic and computational studies. (9th March 2017) - Kubiček, Katharina; Thekku Veedu, Sreevidya; Storozhuk, Darina; Kia, Reza; Techert, Simone
Graphical abstract: Molecular structures of some heteroleptic Cu(I) complexes were calculated using density functional theory. A decreasing ligand steric hindrance facilitates a ligand torsional motion in their excited states (ES). Their experimental ground state (GS) geometric and electronic structures are best reproduced by calculations with density functionals including dispersion and hybrid functionals. Abstract: We have investigated the electronic and geometric structures in the lowest excited states of six phosphorescent heteroleptic [Cu I (NN)(DPEphos)] + (DPEphos = bis[(2-diphenylphosphino)phenyl]ether) complexes with varying NN = diimine ligand structures using density functional theory. In comparison to the ground state, the results show a decrease of the dihedral angle between the N–Cu–N and P–Cu–P planes for these excited states with mixed ligand-to-ligand (DPEphos lone pair → π ∗ (NN)) and metal-to-ligand charge transfer (dπ(Cu) → π ∗ (NN)) character. Sterically less demanding ligands facilitate this process, which is accompanied by a geometric relaxation of the DPEphos ligand and contraction of the Cu–N bonds. The density functional for the excited state calculations has been selected based on ground state validation studies. We evaluated the ability of seven density functionals to reproduce the molecular ground state geometries and absorption spectra obtained by single-crystal X-ray diffraction and solution-phase UV–Vis absorption spectroscopy respectively. Standard methods (PBE and B3LYP), which do not account for dispersion, systematically overestimate internuclear distances. In contrast, approaches including dispersion (B97D3, PBE0-GD3, M06L, M06, ω B97XD) remove this systematic effect and give less expanded molecular structures. We found that only the hybrid functionals (B3LYP, PBE0-GD3, M06), incorporating a portion of exact exchange from Hartree–Fock theory, accurately predict the experimental absorption energies.